Identifying decision-making processes among Malay women entrepreneurs in a fishing area in Tok Bali, Pasir Puteh, Kelantan / Dr. Wan Zumusni Wan Mustapha, Associate Professor Norhaiyati Abd. Muin and Dr. Nik Maheran Nik Muhammad - Wan Mustapha, Wan Zumusni; Abd. Muin, Norhaiyati Abd. Muin; Nik Muhammad, Nik Maheran (2011)
Kelantanese women's entrepreneurial behavior is already well known among the Malaysians. Kelantanese women have been known to be very independent and actively engaged in daily businesses and commercial activities. Therefore, this research seeks to study (1) the factors influencing women of fishing area Tok Bali to involve in entrepreneurship. (2) if the contribution has an impact the economy of their family; (3) whether women in this fishing area have entrepreneurial spirit; (4) If they do, what triggers the entrepreneurial spirit among women in the fishing area of Tok Bali; and (5) how does their performance impact the whole economy in fishing area of Tok Bali. Since women are also the human capital of a nation, it is important that they are no longer marginalized in the nation's development by equipping them with the skills and knowledge to survive in the challenging economy. Using qualitative case study research, the data collection started with a fact finding process for preliminary analysis followed by in-depth interviews with six respondents that have been identified.